Cardiovascular Risk Factors Associated With the Metabolically Healthy Obese (MHO) Phenotype Compared to the Metabolically Unhealthy Obese (MUO) Phenotype in Children - Genovesi, Simonetta; Antolini, Laura; Orlando, Antonina; Gilardini, Luisa; Bertoli, Simona; Giussani, Marco; Invitti, Cecilia; Nava, Elisa; Battaglino, Maria Grazia; Leone, Alessandro; Valsecchi, Maria Grazia; Parati, Gianfranco (Frontiers in Endocrinology, 2020)
Background: In pediatric age the prevalence of obesity is high. Obese children who do not have other risk factors than excess weight have been defined as “metabolically healthy obese” (MHO). Aim: The aim of this study is to evaluate, in a population of obese children, the prevalence of the MHO and “metabolically unhealthy obese” (MUO) phenotype. Furthermore, we evaluated the distribution of Uric Acid, HOMA index and Waist-Height ratio (W-Hr) in the MHO and MUO sub-groups and the impact of these non-traditional risk factors on the probability to be MUO. Methods: In 1201 obese children and adolescents [54% males, age (±SD) 11.9 (±3.0) years] weight, height, waist circumference, systolic (SBP) and diastolic (DBP) blood pressure, pubertal status, glucose, insulin, HDL cholesterol, triglycerides and Uric Acid serum values were assessed. MUO phenotype was defined as the presence of at least one of the following risk factors: SBP or DBP ≥ 90th percentile, glycaemia ≥ 100 mg/dl, HDL cholesterol <40 mg/dl, triglycerides ≥100 mg/dl (children <10 years) or ≥130 mg/dl (children ≥10 years). A multivariate logistic regression analysis was used to estimate the association between MUO phenotype and non-traditional cardiovascular risk factors. Results: The prevalence of the MUO status was high (61%). MUO subjects were more often male, older and pubertal (p < 0.001). The levels of the three non-traditional risk factors were significantly higher in MUO children compared to MHO children (p < 0.001) and all of them were independent predictors of the fact of being MUO [OR 1.41 (95% CI 1.24–1.69); 1.15 (95% CI 1.06–1.23) and 1.03 (95% CI1.01–1.05) for Uric Acid, HOMA index and W-Hr, respectively]. About 15% of MHO subjects had serum Uric Acid, HOMA index and W-Hr values within the highest quartile of the study population. Conclusion: The prevalence of MUO subjects in a large pediatric population is high and serum Uric Acid, HOMA index and W-Hr values are independent predictors of the probability of being MUO. A non-negligible percentage of subjects MHO has high values of all three non-traditional risk factors.